ANALYZING THE IMPACT OF PROMOTION STRATEGIES AND PRICING ON PURCHASE DECISIONS AT MUTIARA FAMILY STORE IN TASIU, MAMUJU DISTRICT - Rini Wahyuni; Muchtar Muchtar; Muh. Ferils (SEAN Institute, 2023)
In this study conducted at Mutiara Family Store in Tasiu, Mamuju District, the impact of promotion strategies and pricing on purchase decisions was examined. The research utilized both quantitative and qualitative data sources, with data collected through observations, interviews, questionnaires, and document analysis. The findings revealed that promotion strategies, including advertising, personal selling, public relations-publicity, and sales promotions, had a positive and significant influence on purchase decisions. Similarly, product pricing, encompassing factors like pricing alignment and perceived value, also exhibited a positive and significant effect on purchase decisions. These results underscore the importance of effective promotional strategies and prudent pricing policies for enhancing customer satisfaction and maximizing sales, offering valuable insights for businesses like Mutiara Family Store in a competitive market.